2012
DOI: 10.3389/fmicb.2012.00133
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Ion Homeostasis by Antifungal Agents

Abstract: Ion-signaling and transduction networks are central to fungal development and virulence because they regulate gene expression, filamentation, host association, and invasion, pathogen stress response and survival. Dysregulation of ion homeostasis rapidly mediates cell death, forming the mechanistic basis by which a growing number of amphipathic but structurally unrelated compounds elicit antifungal activity. Included in this group is carvacrol, a terpenoid phenol that is a prominent component of oregano and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
6
10
0
Order By: Relevance
“…Ongoing projects in our group include, for example, the determination of the role of Ca 2+ during STS-induced cell death. We observed that incubation with this drug (but not PHS) promotes a well-defined profile of alterations in cytosolic Ca 2+ levels, similarly to what is observed when fungal cells are exposed to other cell death stimuli [57]. On the other hand, we are taking advantage of the recent developments on the transcriptomics field and employing high-throughput RNA sequencing (RNA-seq) to study the transcriptional profile of N. crassa cells submitted to different cell death conditions and identify novel cell death intervenients.…”
Section: Discussionsupporting
confidence: 72%
“…Ongoing projects in our group include, for example, the determination of the role of Ca 2+ during STS-induced cell death. We observed that incubation with this drug (but not PHS) promotes a well-defined profile of alterations in cytosolic Ca 2+ levels, similarly to what is observed when fungal cells are exposed to other cell death stimuli [57]. On the other hand, we are taking advantage of the recent developments on the transcriptomics field and employing high-throughput RNA sequencing (RNA-seq) to study the transcriptional profile of N. crassa cells submitted to different cell death conditions and identify novel cell death intervenients.…”
Section: Discussionsupporting
confidence: 72%
“…The time and concentration dependent substantial leakage of K + from treated cell has indicated that cytoplasmic membrane is targeted by test compounds and its fluidity and permeability is changed leading to leakage of cytoplasmic material. Dysregulation of ion homeostasis rapidly mediates cell death, forming the mechanistic basis by which a growing number of amphipathic but structurally unrelated compounds such as terpenoid phenols elicit antifungal activity (Zhang et al 2012 ). Cellular component which absorb light at 260 nm represent one class of leakage components, primarily nucleotides of which uracil containing compounds exhibit strongest absorbance.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of surrounding lipid organization in Pma1 function is also illustrated by the influence of edelfosine, a compound that has high affinity for sterols and disorganizes liquid-ordered membranes (Ausili et al 2018). Incubation of S. cerevisiae with edelfosine causes displacement of Pma1 from DRMs and its ubiquitin-dependent downregulation, thus provoking intracellular acidification and cell death (Zaremberg et al 2005;Zhang, Muend and Rao 2012;Cuesta-Marbán et al 2013;Czyz et al 2013). In Cryptococcus neoformans, Pma1 also fractionates in DRMs (Farnoud et al 2014), and lack of ceramide synthase interferes with Pma1 function and cell growth (Munshi et al 2018).…”
Section: Assembly and Organizationmentioning
confidence: 99%